A geographical information system for wild fire management - Pina, António Manuel Silva (2011)
he CROSS-Fire project focus on developing a grid-based framework for wild fire management using FireStation (FS) as a standalone application that simulates the fire spread over complex topography. The overall software development is made of several components: client applications, which request geo-referenced data and fire spread simulation, Spatial Data Infrastructures (SDI), which provide geo-referenced data, and the GRID, which gives support to the computational and data storage requirements. Herein we present the central WPS (Web Processing System) layer developed to support the interaction between all components of the architecture. This OGC-WS compatible layer provides the mechanism to access the grid facilities for processing and data management and including all the algorithms, calculation, or model that operates on spatially referenced data, also mediating communication with the FS console. We also describe the work that has been done to provide FS with dynamic fuel maps, by using an OGC-WCS suite of services and satellite data. This task complements the previous integration of dynamic data from meteorological stations using OGC-SWE services.